Upaya Pemanfaatan Botol Bekas dalam Pemanfaatan Pekarangan di Dusun Kayuares dengan Metode Vertikultur - Susanti Malasari; Tri Wahyuni; Melinda Diyah Astuti; Tasyanari Handayani; Muhammad Faishal Rahman (FUNDAMENTUM : Jurnal Pengabdian Multidisiplin, 2025)
Plastic waste and the limited amount of agricultural land are big problems for the community, especially in rural areas such as Kayuares Hamlet and Ringinanom Village. The aim of this research is to develop a verticulture technique that uses used bottles to optimize the home yard. Tidar University KKN students provided instruction, training and implementation of a verticulture system using used bottles and PVC pipes. The results of the event show that people are more aware of the importance of using yards and managing plastic waste. In addition, a successfully implemented verticulture system increases land use efficiency and produces vegetable harvests that can help family food security by up to 70%. Limited water resources, high initial costs, and ongoing need for assistance are the main problems in implementing this method. The used bottle-based verticulture system allows communities to continue to develop sustainable agricultural methods that are environmentally friendly and economically profitable.